Nurse's Knowledge Of Telenursing Implementation In Nursing Services - Gandamayu, Ida Bagus Maha; Wahyuningsih, Luh Gde Nita Sri; Sastamidhayani, Putu Amy J (Jurnal EduHealth, 2022)
The development of technology has penetrated the world of health, especially nursing. Telenursing is a form of technology that helps nurses in providing nursing services to patients to be more effective and efficient. This study aims to identify and analyze conflict management for undergraduate nursing students in the implementation of the learning process at the Institute of Technology and Health ( ITEKES) Bali. This study aims to determine nurses' understanding of the implementation of telenursing. A total of 143 people (100%) had a very good understanding of what telenursing is, the benefits, barriers and technicians for implementing telenursing, while for knowledge about forms of telenursing there were still some respondents who did not know about other forms of telenursing as many as 43 people (30.07 %).The results of this study indicate that nurses already have good knowledge about the implementation of telenursing.